Cobalt-free perovskite Ba1-xNdxFeO3-δ air electrode materials for reversible solid oxide cells. Issue 6 (15th March 2021) - Kim, You-Dong; Yang, Ja-Yoon; Saqib, Muhammad; Park, Kwangho; Shin, Ji-seop; Jo, Minkyoung; Park, Kwang Min; Lim, Hyung-Tae; Song, Sun-Ju; Park, Jun-Young
Abstract: We report on Ba1-x Ndx FeO3-δ, a cobalt-free perovskite material, with a view to its use as a next-generation air electrode material in reversible solid oxide cells (RSOCs). BaFeO3-δ (BFO) has long been considered a potential candidate cathode material due to its high oxygen vacancy concentration and electrical conductivity; however, it is difficult to synthesize in a single phase. To overcome this problem, Nd 3+ is doped into Ba-sites to reduce impurity phases and create a single perovskite phase. In-situ high temperature and room temperature X-ray diffraction analyses are carried out to investigate Nd 3+ -doped BFO. We find that Ba0.97 Nd0.03 FeO3-δ shows the highest electronic conductivity and lowest TEC value among the various doping concentrations tested, making this material most suitable for application in RSOCs. In addition, the polarization resistance of Ba0.97 Nd0.03 FeO3-δ has the lowest value in yttria-stabilized zirconia symmetric cells. To determine the reasons for the high catalytic activity of Ba0.97 Nd0.03 FeO3-δ, X-ray photoelectron spectroscopy and iodometric titration are carried out, the results demonstrate that the lower doping concentration of Nd 3+ results in an advantage in terms of the number of additional oxygen vacancies created. Moreover, electrical conductivity relaxation measurements show that the Ba0.97 Nd0.03 FeO3-δ has a fast bulk diffusion coefficient and fast surface exchange coefficient. Hence, the solid oxide fuel cell and electrolysis mode performances when using Ba0.97 Nd0.03 FeO3-δ are excellent and a high power output of 1.2 W cm −2 at 800 °C can be achieved.